1989
DOI: 10.1002/mar.4220060305
|View full text |Cite
|
Sign up to set email alerts
|

Temporal decay in satisfaction – Purchase intention relationship

Abstract: It was hypothesized and empirically confirmed that brand attribute information is salient in predicting immediate satisfaction and that these factors strongly influence intentions formed immediately after product trial. However, it was shown that in delayed measurement, past knowledge factors increasingly become salient while the relative explanatory power of performance evaluation and satisfaction decays in forming future purchase decisions. The impact of the timing factor and the strategic implications of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
5

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 27 publications
5
38
0
5
Order By: Relevance
“…Regarding links f and g, most research has been performed on a cross-sectional basis with the assumption that satisfaction in Tl directly affects satisfaction in T2. However, the only study (Mazursky and Geva 1989) to examine such a direct link on a longitudinal basis finds no support for such a link. Regarding the temporal impact of intentions (links d and e), though some evidence exists to show that prepurchase intentions affect postpurchase intentions (LaBarbera and Mazursky 1983; Oliver 1980), no study has examined the dynamics of postpurchase intentions.…”
Section: The Dynamics Of the Satisfaction-intention Linkmentioning
confidence: 88%
“…Regarding links f and g, most research has been performed on a cross-sectional basis with the assumption that satisfaction in Tl directly affects satisfaction in T2. However, the only study (Mazursky and Geva 1989) to examine such a direct link on a longitudinal basis finds no support for such a link. Regarding the temporal impact of intentions (links d and e), though some evidence exists to show that prepurchase intentions affect postpurchase intentions (LaBarbera and Mazursky 1983; Oliver 1980), no study has examined the dynamics of postpurchase intentions.…”
Section: The Dynamics Of the Satisfaction-intention Linkmentioning
confidence: 88%
“…Several problems in interpretation arise through the use of a satisfaction measure and an intentional measure of loyalty in the same survey: common-method variance may inflate the relationship. Mazursky and Geva (1989) found that satisfaction and intentions ratings were highly correlated when measured at the same time but had no correlation when measured at two different points in time. Additionally both ratings may be influenced by the same response bias thereby leading to spurious correlations (Arnold, Feldman, & Purbhoo, 1985;Zedeck, Kafry, & Jacobs, 1976).…”
Section: Theoretical Backgroundmentioning
confidence: 90%
“…There are theoretical reasons for believing that an attitude developed as a result of a service encounter may change with the passage of time, supported by increasing empirical evidence (Mazursky and Geva 1989;Verhoef et al 2000). One scenario is that we look back at an encounter increasingly favourably through what has been described as "rose-tinted spectacles".…”
Section: Attitude Change Over Timementioning
confidence: 99%